SUNDANESE INDIGENOUS KNOWLEDGE IN SINDANG BARANG CULTURAL VILLAGE – BOGOR - Rizki Nurislaminingsih; Arido Laksono; Eka Purna Yudha (Sanata Dharma University, 2022)
The Sindang Barang Cultural Village was formed by the descendants of customary holders who live in Bogor to revitalize Sundanese culture. This is useful for preserving customs so that people can continue to live the Sundanese way (using indigenous knowledge and sticking to local wisdom) even though they live in the modern era. This study aims to identify the Sundanese indigenous knowledge possessed by them. This study uses a qualitative thematic analysis approach to identify it. The results of this study indicate that the themes of indigenous knowledge owned by the society are village landscape, agriculture, natural signs, health, and batik. The village landscape has sub-themes landscape of land and building position. The sub-themes of agriculture are the type of paddy, fertilizer, planting time, magic guard, and granary. Natural signs have the sub-themes of changing days and signs of calamity and disaster. The sub-theme of health is herbs. Batik has a sub-theme of motifs and natural dyes. This study found that some of the indigenous knowledge about herbs and batik had been lost from the people's memory.